UPAYA PENANGGULANGAN HUKUM TERHADAP ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA MELALUI PENEGAKAN KODE ETIK PROFESI POLRI - Dr. Nanang Solihin; satria dwie rahardja (VERITAS, 2018)
The condition is often preached in various mass media law violations committed bypolice officers, such as the number of cases of drug abuse by members of thepolice, the police officers involved in criminal, arbitrary police officers, and manyother cases that describe the lack of discipline police officers, make its ownconcern for the people involved in the implementation of the main tasks of thepolice are to maintain security and public order, orderly and law enforcement, theimplementation of protection, guardianship, and service to society, and terbinanyapeace of the community by upholding human rights. The purpose of this study wasto determine how the Legal Efforts Against Members of the Police Crime ThroughConducting Enforcement Police Code of Ethics, and other objective is to knowabout the mechanism of the implementation of legal sanctions Code of Conduct forpolice officers who commit crimes and offenses - violations of law in the effort tostrengthen the image of the Police. This research is descriptive and includes viewsof the purpose of empirical legal research. What research was conducted at theNational Police Agency. The type of data used include primary data and secondarydata. The technique of collecting data through interviews and library research bothbooks, legislation, papers, results of previous studies, documents, etc.